PENERAPAN MODEL PEMELAJARAN PROBLEM SOLVING UNTUK MENINGKATKAN HIGHER ORDER THINKING SKILLS (HOTS) PADA PEMBELAJARAN IPAS SEKOLAH DASAR - Delvi Liani, Dea; Ananda, Rizki; Rahma Rani, Afriza; Indra Daulay, Musnar; Aprinawati, Iis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low Higher Order Thinking Skills (HOTS) in learning science in class IV UPT SDN 017 Langgini. One solution to overcome this problem is to use the problem solving model. This study aims to improve Higher Order Thinking Skills (HOTS) using the problem solving model in class IV UPT SDN 017 Langgini students. This research method is classroom action research (PTK) which is carried out in two cycles consisting of two meetings and four stages, namely planning implementation, observation, and reflection. The time of this research was carried out in may dan july 2024. The subjects of this research were students of class IV UPT SDN 017 Langgini. Consists of 12 students, there are 4 male students and 8 female students. Methods of data collection using observation techniques and documentation techniques. The result of the study show that using the problem solving learning model can improve students Higher Order Thinking Skills (HOTS). This is shown by the acquisition of observation in the first cycle of the second meeting of 12 students, it is known that the Higher Order Thinking Skills (HOTS) of students included in the complete category reach 4 people or 34% and in the first cycle of the second meeting there are 5 people 42%. Then in cycle II meeting I there were 7 people or 59% who experienced completeness and in cycle II meeting II it increased to 10 people or 84. Through the applivation of problem solving models in improving the Higher Order Thinking Skills (HOTS) of class IV UPT SDN 017 Langgini students.